ANALYSIS OF DRUGS EFFECTS ON QTc INTERVAL PROLONGATION IN CRITICALLY ILL PATIENTS IN INTENSIVE CARE UNITS - Golić, Slavko (Medicinski podmladak, 2025)
Introduction: QTc interval is considered extended if its duration is longer than 450ms for men, or 460ms for women. QTc prolongation is an often underdiagnosed condition whose prevalence is likely higher than clinicians realize. Many drugs can prolong the QTc interval.The aim: The aim of this study was to analyze the impact of drug interactions on prolonging the QTc interval in critically ill patients.Material and Methods: It is a cross-sectional observational study with retrospective datacollection of adult patients admitted to one of the three intensive care units (ICU) of the ``Bezanijska kosa`` Hospital in the period from April to September 2022. To identify risk factors for the development of a prolonged QTc interval, patient variables were compared between patients with a prolonged and those with normal QTc interval.Results: 166 patients of average age 70.7±12.2 years were included in the study of whom45.2% were women. The prevalence of QTc interval prolongation was 71/166, i.e. 42.8% (95% CI=35.1%-50.7%), 50.5% (95% CI=39.9%-61.2%) in men and 33.3% (95% CI=22.9%-45.2%) in women (p=0.12). During the stay in ICU, 32 patients had a prescription of 2 drugs for which is known that are connected with QTc interval prolongation (19.3%, 95% CI=13.6% -26.1%). In patients with prolonged QTc interval, 27/32 (84.4%, 95% CI=67.2%-94.7%) received drugs which are connected with QTc prolongation while 5/32 patients with normal QTc interval duration (15.6%, 95% CI=5.3%-32.8%) received drugs which are connected with its prolongation.Conclusion: Our study showed a high prevalence of prolonged QTc interval in critically ill patients and pointed to the most likely existence of a higher risk of its prolongation when drugs whose interaction can lead to the its prolongation are used at the same time.
Keywords: QTc interval; intensive care units; drugs interactions